Blended Learning as the Best Scenario for Institutions Affected by Massification - Boutarti, Sana; Berrada, Khalid; Burgos, Daniel (Lecture Notes in Educational Technology, 2023)
Massification is a problem affecting universities around the world, given the increase in student enrolments. Teaching in a large classroom containing a huge number of students is a great challenge for teachers. Cadi Ayyad University (UCA) is no exception; like all universities in Morocco, especially open-access institutions, it deals with the phenomenon of overcrowding in amphitheatres. Faced with this problem, UCA needs solutions to ensure adequate learning to improve student engagement in this process. In this chapter, we will focus on the blended learning or hybrid learning approach as a solution to massification in UCA’s faculties. We will shed light on some studies and projects carried out based on this approach while showing the effectiveness of blended learning for improving student engagement and learning in the context of large classes.
Keywords: blended learning; instructional technology; large classes; massification; platform; student engagement; universal design for learning; Scopus(2)